The Use and the Frequency of Arabic Loan Words in the Turkish Language - Vulović, Aleksandra M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The presence of a large number of Arabic loan words in modern Turkish is the consequence of close language contacts which started with the Islamisation of the Turks. In the beginning, that influence was evident in the domain of religious terminology during the process of acquiring a new faith, but it soon grew into uncontrollable borrowing given that the Arabic language was once the language of science as well. Although the number of Arabic and Persian words was the biggest, the Turkish language vocabulary consisted of French, Italian, Greek, and German words as well. Going through its developmental phases, mixing the Turkish, Arabic and Persian linguistic elements, a hybrid language was created. By the creation of the Ottoman Turkish language, the lexical domain of the language was greatly changed and it contained the least amount of Turkish words at that time. When the Republic of Turkey was established, it was necessary to gain linguistic independence and to weed out the foreign words from the language. After these language purist movements, the Turkish language was free from loan words, but still there are those words that are deeply rooted in the Turkish language corpus, and these words are mostly Arabic.The use of Arabic loan words is most effective in the domain of legal and administrative language register, given that in these segments no linguistic puritanism was executed. Arabic words have a significant role in phrases and proverbs, where they survived despite the attempts for them to be replaced by Turkish equivalents. Even though Arabic loan words hold an important place in the Turkish language, given their position in religious terminology, the phenomenon of reviving many Arabic words in the Turkish language is interesting. As the development of a language is a crucial social factor, it could be said that in Turkish, because of a more conservative political current, more and more of the forgotten Arabic terms are being used. By the language purification process, numerous Arabic loan words were suppressed, but lately the members of the party in power have been using Arabic loan words in their addresses. As a consequence of this and since these words are unfamiliar to the wider public, their number in the modern Turkish language has started to increase.
Keywords: the Turkish language; loan words; Arabic loan words; linguistic purism